2022
DOI: 10.3390/microorganisms10020480
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Assessment of DNA Viral Diversity in Freshwater Sponges, Baikalospongia bacillifera

Abstract: Sponges (type Porifera) are multicellular organisms that give shelter to a variety of microorganisms: fungi, algae, archaea, bacteria, and viruses. The studies concerning the composition of viral communities in sponges have appeared rather recently, and the diversity and role of viruses in sponge holobionts remain largely undisclosed. In this study, we assessed the diversity of DNA viruses in the associated community of the Baikal endemic sponge, Baikalospongia bacillifera, using a metagenomic approach, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 99 publications
2
9
0
2
Order By: Relevance
“…Newly identified viruses from Baikal mollusks have expanded the unique diversity of viruses previously discovered in the waters of Lake Baikal [86,87] and in the endemic Baikal sponges [69,72]. The viral diversity in Baikal endemic gastropods B. baicalensis included the unknown representatives of different orders and families and of two main phyloge-netic branches [37].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Newly identified viruses from Baikal mollusks have expanded the unique diversity of viruses previously discovered in the waters of Lake Baikal [86,87] and in the endemic Baikal sponges [69,72]. The viral diversity in Baikal endemic gastropods B. baicalensis included the unknown representatives of different orders and families and of two main phyloge-netic branches [37].…”
Section: Discussionmentioning
confidence: 85%
“…All Baikal mollusk metatranscriptomic data (Table 1) were aggregated into one array for de novo cross-assembly as recommended in other viral community studies [72]. For cross-assembly, the MEGAHIT v.1.2.9 NGS assembler optimized for metagenomics was used with default options [34].…”
Section: Assembly Of Metatranscriptomic Readsmentioning
confidence: 99%
“…Reads related to virophages predominated in the MSC sample, as did those related to mimiviruses. Other studies of viromes [46,[74][75][76] showed that virophages are widely spread throughout the world in a variety of environments, both marine and freshwater. In addition to virophages and tailed phages, viruses of seven other different families were quantitatively predominant in the MSC compared to the SUR and SBI samples.…”
Section: Discussionmentioning
confidence: 99%
“…All the genomic data (Table 1) were aggregated into one array for de novo crossassembly as recommended [46]. For cross-assembly, the MEGAHIT assembler was used with default options [49].…”
Section: Assembly Of Virome Readsmentioning
confidence: 99%
“…Существует другой подход, при котором после фильтрации по качеству наборов данных из нескольких образцов все прочтения объединяются в один массив и производится единая de novo сборка («cross-assembly»). В наших предыдущих метавиромных исследованиях мы использовали этот подход для сравнения вирусного разнообразия нескольких образцов [16][17][18]. В полученной геномной сборке (далее микс-сборке) скаффолды тестируются одним из алгоритмов на основе HMM метода для поиска потенциальных фрагментов вирусных геномов (фрагментов геномов РНКсодержащих вирусов и транскрибируемых генов ДНК-содержащих вирусов в случае метатранскриптомов).…”
Section: Introductionunclassified